The Roles of Mentor to Maintain The Ciputra University Students Business Sustainability - Effendy, Junko Alessandro (Review of Management and Entrepreneurship, 2018)
Ciputra University is a private institution established with expectation to boost the economic rate of Indonesia. The graduates of Ciputra Universityare expected to become entrepreneurs with positive contributions for the country. The students are encouraged to start up their business in their second semester and to sustain their business until they graduate. Each business project is being assisted by a mentor to help the growth. However, fact showed that the number of sustainable business was small. This research aims to discuss about how to maximize the roles of mentor in order to maintain the Ciputra University students’ business sustainability. The research was done qualitatively by implementing semistructured interviews to eight respondents with three different criteria. The results showed that to become a mentor that can maintain the students’ business sustainability, one must possess three aspects: an observant personality, a problem solver, and with years of experience.